Relationship Between Phospholipid Biosynthesis and the Efficiency of the Arsenate Transport System in Yeasts - Cerbón, Jorge (1970)
In studying the possibility that phosphoinositides which formed complexes with arsenic were involved in the arsenate transport system of yeasts, a comparative study of the phospholipid composition and metabolism was carried out both in Saccharomyces carslbergensis and in its arsenate-adapted variant, which showed a deficient inflow of arsenate. It was found that the lipid composition of the two organisms was quite similar, the main classes of phospholipids being phosphatidylcholine, phosphatidylethanolamine, and phosphoinositides. The only difference was a 1.5- to 2-fold increase in the proportion of inositides in the arsenate-adapted cells. When the transport of arsenate became inactivated in the nonadapted yeasts after a 30- to 60-min exposure to 10(−2)m arsenate, an increment of inositides of 29 to 50% over the original level was also detected. A study of the incorporation of radioactivity from uniformly labeled (14)C-maltose and from (32)P-orthophosphate ((32)P(i)) demonstrated a decreased rate of lipid biosynthesis in the arsenate-adapted cells as compared to the normal nonadapted ones. The turnover of the phosphate in phospholipids demonstrated no turnover in phosphatidylcholine and phosphatidylethanolamine, and a slow turnover in phosphoinositides. It could be inferred that a normal rate of phospholipid (phosphoinositides) biosynthesis is necessary to have a normal arsenate uptake and that inositide accumulation impairs both the mechanism responsible for the uptake and accumulation of arsenate and the rate of lipid biosynthesis. No differences were found in the deoxyribonucleic acid or protein content of the two types of cells. Also, the arsenate-adapted cells, once freed of external arsenate, showed an increased uptake of (32)P(i) from low external concentrations of phosphate (10(−6) to 10(−8)m, 10-fold over that observed in AsS cells). These results are indicative of independent behavior in phosphate and arsenate transport systems.